MIKROENKAPSULASI PIGMEN BETA-KAROTEN DENGAN METODE FOAM MAT DRYING MENGGUNAKAN GELATIN TULANG IKAN KAKAP MERAH SEBAGAI BAHAN PENYALUT - Mei Linda Nikma Nur Ulumi; Dwi Syanti Wirandhani; Reza Fadilah Ardhani; Cathrine Olivia Andhani; Desiana Nuriza Putri (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Carrots (Daucus carota L.) are vegetables of the Apiaceae family that contain carotenoids, flavonoids, polyacetylenes, vitamins, and antioxidants. One of the carotenoid derivative compounds is beta-carotene. However, neither carotenoids nor their derivatives are stable on oxidation and easily degraded when exposed to light, oxygen, acids, and heat during food processing and storage. Microencapsulation with foam-mat drying method is an alternative to maintain the stability of beta carotene pigments. The research aimed to study the effects of the red-snapper bone gelatin and maltodextrin ratios on characteristics of the encapsulated β-carotene. This research is used as a reference for literature regarding the development of halal gelatin and its application as a coating material for pigment microencapsulation. This research used a randomized block design with one factor, the ratios of gelatin and maltodextrin were GM 1 (1:1); GM 2 (1:1.5), GM 3 (1:2), and GM 4 (1:2.5). The results of the research showed that the ratio factors of gelatin and maltodextrin had a real impact on yield, water content, total carotenoids, surface carotenoids, solubility, encapsulation efficiency, rehydration ratio, bulk density, color intensity, and morphological observation using an optical microscope. The results showed the best treatment resulted in the ratio of the GM 1 (1:1) with the yield of 9.84 percent, the water content of 8.8 percent, total carotenoids of 203.85 mg/g, surface carotenoids of 2.01 mg/g, the solubility of 63.67percent, encapsulation efficiency of 99.15 percent the rehydration ratio of 259.70 percent, the bulk density of 0.3532 g/m, and color intensity (L: 46.6; a+: 28.1 and b+: 19.2). Red snapper bone has the potential to be used as a source of gelatin which has high encapsulation efficiency.